The Influence of Self-Disclosure and Social Media Addiction on Social Anxiety in Emerging Adults Users of Instagram Close Friend Feature - Ambarwati, Septiana; El-Fikri, Dewi Nabela Sofya; Setiyaji, Nanda Ridwan (Journal of Cultural Narratives in Digital Society, 2025)
This study aims to examine the effect of self-disclosure and social media addiction on social anxiety in emerging adult users of Instagram's close friends feature among students in Semarang, in accordance with the formulation of the problem which aims to determine whether the two independent variables have a significant effect on the dependent variable. This study uses a quantitative method and a sample of 176 students, the study collected data through an online questionnaire (google form) with a Likert scale and analyzed using multiple linear regression. The results show that social media addiction has a significant effect on social anxiety (p <0.05, coefficient 0.5138), while self-disclosure does not have a significant effect, with the majority of respondents in the moderate category to the third variable. This study proves that social media addiction has an important role in increasing social anxiety in emerging adults in the digital era, contributing to understanding the psychological dynamics of social media users.